Fungicidal control of Sclerotium basal rot of cluster bean cv. Pusa Naubahar - GANESHAN, GIRlJA (Indian Phytopathology, 2002)
Eleven fungicides were screened in vitro against S. rolfsii [Corticium rolfsii] which causes basal stem rot in cluster bean (Cyamopsis tetragonoloba) cv. Pusa Naubahar. 0.2% Quintozene (as Brassicol), 0.1% mancozeb (as Dithane M-45), 0.2% captafol (as Foltaf) and 0.2% thiram (as Thiride) were effective in completely inhibiting fungal growth. Among the different methods of fungicidal application, seed treatment by soaking seeds overnight in a 0.2% solution of mancozeb produced a final crop stand of43%. Mancozeb and captafol when administered as soil dry mix gave up to 75 and 77% control, respectively. Quintozene applied as a soil drench twice, 4 days prior to sowing of seeds at an interval of 5 days gave up to 73% disease control. The other methods of application were ineffective.